Diffusion of Innovations and Public Communication Campaigns: An Examination of The 4R Nutrient Stewardship Program - Henry Seeger; Robyn S Wilson (Journal of Applied Communications, 2019)
This project is an examination of how strategies for innovation in fertilizer application are communicated to agricultural communities. Specifically, this project examines the 4R Nutrient Stewardship Program‒a public communication campaign seeking to encourage the use of specific strategies, tools, and best practices in fertilizer application. The campaign is advanced by the Fertilizer Institute, an industry trade association, and targets local agricultural communities within the United States. To understand how this campaign functions to encourage adoption of innovative fertilizer application behaviors, this project draws on the principles of diffusion of innovations theory as well as established concepts within public relations, including issues management.
Keywords: Public Communication Campaigns; Diffusion of Innovations; Fertilizer Runoff; Water Contamination